Loxoscelismo cutáneo-visceral pediátrico con lesión aguda renaly distrés respiratorio: reporte de caso - Rivero Angeles, Mercedes (2026)
Cutaneous-visceral loxoscelism (CVL) is a pediatric emergency with a high case-fatality rate.This report highlights the clinical suspicion of diffuse alveolar hemorrhage (DAH) associated with renal failure, a complication suggesting severe systemic endothelial injury caused by the venom. A 6-year-old girl presented 24 hours after a spider bite with a livedoid plaque,jaundice, and respiratory distress. Laboratory tests confirmed severe hemolytic anemia (Hb, 8.0 g/dL), coagulopathy, and acute kidney injury (creatinine, 3.18 mg/dL). The diagnosis was CVL with renal failure and suspected DAH based on hemoptysis, a drop in Hb to 6.5 g/dL, and new pulmonary infiltrates, as patient instability precluded bronchoscopy. Anti-Loxosceles antivenom was administered 15 hours after the bite, along with critical care support including mechanical ventilation, hemodialysis, followed by skin autografting. The clinical picture consistent with DAH resolved, and complete renal recovery was achieved. The patient was discharged on day 45 without systemic sequelae. Survival in the presence of atypical and potentially fatal systemic complications of loxoscelism depends on early clinical recognition and intensive multiorgan supportive care, even when patient instability limits definitive diagnostic procedures.